2015
DOI: 10.4082/kjfm.2015.36.6.316
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Factors Associated with Albuminuria according to Gender and Comorbidities of Hypertension and Diabetes

Abstract: BackgroundThis study examined the differences in factors associated with albuminuria according to gender and comorbidities of hypertension (HTN) and diabetes mellitus (DM).MethodsWe included 3,859 participants aged 20 to 79 years (55% female) from the 5th Korea National Health and Nutrition Examination Survey. Participants were excluded if they took antihypertensive or anti-diabetic medication, had chronic renal failure, had malignant tumor, were pregnant or menstruating during the health examination, or had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although, the reason for this remains unclear, it is likely that the gender differences (M:F of 9:17 in the DR group compared to 14:15 in no DR group) were the contributing factors. One of the previous studies has suggested that factors that correlate with albuminuria were different for men and women according to comorbidities such as hypertension and diabetes [ 29 ]. Additionally, other factors that may have contributed include the severity of DR and nephropathy, ongoing medications as well as the glycaemic control, although a positive correlation with HbA1c level was not evident in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the reason for this remains unclear, it is likely that the gender differences (M:F of 9:17 in the DR group compared to 14:15 in no DR group) were the contributing factors. One of the previous studies has suggested that factors that correlate with albuminuria were different for men and women according to comorbidities such as hypertension and diabetes [ 29 ]. Additionally, other factors that may have contributed include the severity of DR and nephropathy, ongoing medications as well as the glycaemic control, although a positive correlation with HbA1c level was not evident in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of albuminuria differ among males and females and may also be driven by underlying chronic medical conditions 27 . Several studies have shown that PLWH with diabetes mellitus have a significantly higher prevalence of albuminuria [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…Albuminuria is not only a prognostic marker for renal disease, but also a significant predictor of cardiovascular disease and all-cause mortality [ 1 , 2 ]. Because of its broad range of implications, albuminuria itself has been targeted as a therapeutic goal to prevent the progression of certain medical conditions [ 1 - 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, the association between vitamin D deficiency and albuminuria in the general population in Korea has not yet been investigated. Moreover, since sex has strong effects on the prevalence of albuminuria and on vitamin D metabolism [ 2 , 19 ], it is necessary to explore whether sex has confounding effects or interaction effects on the association between these 2 variables. The aim of our study was to assess the association between low serum vitamin D levels and albuminuria separately by sex in the Korean general population.…”
Section: Introductionmentioning
confidence: 99%